Bio-similar drug development and accessible drugs in the market for the treatment of Alzheimer's Disease: Current status - Tamanna, Mst. Taskia (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2022.